The Effectiveness of Acupuncture Therapy and Acupressure Therapy as an Effort to Lower Blood Pressure in Hypertension in Productive Age - Betharia Mardiyani; Yuly Peristiowati; Hariyono (Universitas STRADA Indonesia, 2024)
Background: Hypertension in productive age has become a health threat for all of us. In addition to the use of medical treatment for people with hypertension, hypertension can also be done with complementary therapies which are more effective and do not cause side effects in the treatment of hypertension. Complementary therapies that can be used are acupuncture and acupressure therapy. Purpose: Analyzing the effectiveness of acupuncture and acupressure therapy in reducing high blood pressure in the productive age population Methods: The method used in this study was a quasi-experimental study with a one group pretest and posttest design. This study was conducted on 24 samples by comparing the experimental class 1 which used acupuncture therapy, the experimental class 2 which used acupressure therapy and the control class which was not given any treatment, then an evaluation was carried out and the results were compared. Conclusion: Patients who used acupuncture therapy experienced a decrease in systolic blood pressure with a value of 17.73% and diastolic blood pressure with a value of 16.44% faster in reducing blood pressure compared to acupressure therapy which had an average value of 13.38% for systolic blood pressure . and 14.19% for diastolic blood pressure. By looking at these results it can be obtained that the most effective therapy in reducing high blood pressure is acupuncture therapy.